Characterizing Glioblastoma Heterogeneity via Single-Cell Receptor Quantification - Chen, Si; Le, Thien; Harley, Brendan A. C.; Imoukhuede, P. I. (Frontiers in Bioengineering and Biotechnology, 2018)
Dysregulation of tyrosine kinase receptor (RTK) signaling pathways play important roles in glioblastoma (GBM). However, therapies targeting these signaling pathways have not been successful, partially because of drug resistance. Increasing evidence suggests that tumor heterogeneity, more specifically, GBM-associated stem and endothelial cell heterogeneity, may contribute to drug resistance. In this perspective article, we introduce a high-throughput, quantitative approach to profile plasma membrane RTKs on single cells. First, we review the roles of RTKs in cancer. Then, we discuss the sources of cell heterogeneity in GBM, providing context to the key cells directing resistance to drugs. Finally, we present our provisionally patented qFlow cytometry approach, and report results of a “proof of concept” patient-derived xenograft GBM study.